Analysis of timber beams reinforced with FRP bars using the NSM technique - Assis, Letícia Freitas [UNESP]; Pedreiro, Marcelo Rodrigo de Matos [UNESP]; Jardim, Pedro Ignácio Lima Gadêlha; Dos Santos, Herisson Ferreira; Christoforo, André Luis (FapUNIFESP (SciELO), 2024)
Timber is a material that has been widely used in structures since ancient times, but because it is an organic material, its properties vary greatly, which can have an impact on structural performance. Strengthening with fiber-reinforced polymer (FRP) composites, especially using the NSM technique, offers significant improvements in the mechanical properties of timber structures. Some studies have evaluated the effect of using different fibers, as well as different arrangements of the bars in the cross-section. Even so, the structural contribution obtained by adopting different types of fibers as strengthening in timber beams and using bars in the lower and upper faces of the beam cross-section has not yet been widely evaluated. The aim of this study was to investigate the impact of adding bars in the compressed region and the type of fiber on the stiffness and load capacity of timber beams. To this end, a parametric study was carried out using numerical simulation in finite element analysis software. The results showed that a strengthening rate of 1% increased the beam's load-bearing capacity by up to 14.25%, similar to that obtained in other studies with higher strengthening rates, but with different bar arrangements. CFRP bars provided the best results, followed by GFRP and BFRP bars respectively.
Análise de vigas de madeira reforçadas com barras de FRP pela técnica NSM
Keywords: Composite materials; Fiber-reinforced polymers; Numerical analysis; Structural recovery